Ustrój gospodarczy w nowej Konstytucji - Suchocka, Hanna (Wydział Prawa i Administracji UAM, 1995)
The reader's attention is drawn to the fact that in view of a negative reaction to the concept of "socialistic law", there is a tendency to limit the provisions of the Constitution in the area of the economic regime. Though the regulation of these matters is necessary it should not be too detailed. The Constitution onght to contain the basic principles of the budget law and regulate the status of the National Bank of Poland. It should be based on the principle of subsidiarity and be guided by economic realism indicating the economic policy of the state, rather than formulating subjective laws incapable of being enforced.
Constitutional principles of the economic system